2013
DOI: 10.1080/03949370.2012.705331
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the acoustic behaviour of red deer during breeding in a wild alpine population, and implications for species survey

Abstract: A necessary step in the application of animal communication studies to population ecology involves quantitative descriptions of acoustic variation within individuals. Stereotypy is in fact fundamental to allow individual recognition based on call structure and, in turn, to establish the number of different calling individuals in a population (complementing censuses), or to track individuals through years by the acoustic characteristics of their signals (complementing monitoring). Here we centred on the acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
2
17
0
2
Order By: Relevance
“…Mazzarone et al (1991), per le Foreste Casentinesi, hanno riscontrato che il picco della frequenza dei bramiti si colloca nell'ultima settimana di settembre nelle ore comprese tra le 21 e le 24 e tra le 3 e le 6. Bocci et al (2012) indicano che l'attività di bramito mostra un picco 5-7 ore dopo il tramonto.…”
Section: Sessioni DI Ascolto Continuatounclassified
See 1 more Smart Citation
“…Mazzarone et al (1991), per le Foreste Casentinesi, hanno riscontrato che il picco della frequenza dei bramiti si colloca nell'ultima settimana di settembre nelle ore comprese tra le 21 e le 24 e tra le 3 e le 6. Bocci et al (2012) indicano che l'attività di bramito mostra un picco 5-7 ore dopo il tramonto.…”
Section: Sessioni DI Ascolto Continuatounclassified
“…La necessità di effettuare una o più repliche è evidenziata anche da Bocci et al(2012), che suggeriscono che l'analisi spettrografica dei suoni emessi durante il periodo del bramito potrebbe migliorare l'applicazione di questo metodo, evitando doppi conteggi di maschi in bramito che si spostano durante la sessione di rilevamento.…”
Section: La Conta Dei Maschi In Bramitounclassified
“…As a consequence, vocalizations of Siberian wapiti are much more similar to those of American wapiti than to European red deer (Tembrock, 1965;Nikolski & Wallschlager, 1983;Volodin et al, 2013). European red deer stags produce low-pitched roars with fundamental frequency (f0) ranges from 40 to 380 Hz: Corsican C. e. corsicanus Erxleben, 1777 (mean f0 = 40 Hz: Kidjo et al, 2008); Scottish C. e. scoticus Lonnbert, 1906 (mean f0 = 107 174 Hz: Long et al, 1998;Reby & McComb, 2003); Iberian C. e. hispanicus Hilzheimer, 1909 (mean f0 = 180 186 Hz: Frey et al, 2012;Passilongo et al, 2013); C. e. hippelaphus Erxleben, 1777 (maximum f0 = 273 Hz: Bocci et al, 2013). In contrast, the available data for American and Siberian wapiti suggest produce high-pitched bugles with an f0 above 1000 Hz: Siberian wapiti from Altai C. e. sibiricus (Nikol skii, 2011); Canadian wapiti C. e. canadensis (Struhsaker, 1968); Roosevelt wapiti C. e. roosevelti Merrian, 1897 (Bowyer & Kitchen, 1987), Tule wapiti C. e. nannodes Merriam, 1905(Volodin et al, 2013 and Rocky Mountain wapiti C. e. nelsoni Bailey, 1935 (Feighny et al, 2006;Frey & Riede, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of temperature on the vocal activity of stags in the wildlife Alpine population was also absent [13], while a 31 year study in France has demonstrated a negative correlation between ambient temperature and the counted rutting calls. This is explainable by a decrease in animal activity with increase in temperature [11].…”
Section: Resultsmentioning
confidence: 99%
“…In the Alpine population (Italy), stags mainly roared in the night and early morning (5 a.m. to 7 a.m.) [13]. However, the stags of the Isle of Rum red deer [14] roared mainly during daytime, as did farmed red deer stags in France [15].…”
Section: Resultsmentioning
confidence: 99%